Pengembangan Media Card Match Circle (CMC) pada Pembelajaran IPAS Materi Metamorfosis untuk Meningkatkan Pemahaman Siswa Kelas III MI Roudlotul Ulum Pasuruan - Siti Nur Fariga Huma Khasanah; Erfan Efendi (INDO PUBLISHING, 2026)
Selecting learning media that aligns with the characteristics of elementary school students is an important factor in creating active and meaningful learning. Based on observations and interviews conducted in Grade III at MI Roudlotul Ulum Pasuruan, IPAS learning on metamorphosis material was still dominated by conventional methods, resulting in limited student participation, collaboration, and understanding. In addition, the limited use of learning media caused students to be less enthusiastic during the learning process. This study aimed to describe the development process, feasibility, and effectiveness of the Card Match Circle (CMC) learning media. The research employed the Research and Development (R&D) method using the ADDIE model. Trials were conducted on a small scale involving 5 students and a large scale involving 20 students. Data collection techniques included observation, interviews, questionnaires, documentation, and tests. The results showed that the CMC media obtained a validation score of 85% from media experts and 90% from material and learning experts, categorized as highly feasible. The Wilcoxon Signed Rank Test showed an Asymp. Sig. (2-tailed) value of 0.000 < 0.05, while the N-Gain score was 0.80 with a percentage of 79.69%, indicating that the CMC media was effective in improving students’ understanding of metamorphosis material.